Brain Mr Imaging With A T1-Weighted Image Fluid Attenuated Inversion Recovery Sequence : Comparison Study With T1-Weighted Image Spin Echo Sequence - Fatimah Fatimah; Rini Indrati; Adjie Suroso (Jurnal Riset Kesehatan, 2012)
The purpose of this research to find out the differences between T1-Weighted Image Fluid Attenuated Inversion Recovery (T1WI FLAIR) and T1-Weighted Image Spin Echo (T1WI SE) sequences, use with MRI Superconducting Modality 0,5 Tesla and to determine its superiority between those sequences, at low field strengths.  This is experimental research. Twenty four patients with brain lesions underwent T1-Weighted Image Spin Echo and T1-Weighted FLAIR imaging during the same imaging session. T1-Weighted Spin Echo and T1-Weighted FLAIR Images were compared on the basis their SNR and CNR. Data were analysed statistically using t-test and Mann-Whitney test. Contrast to Noise Ratio (CNRs)  obtained with T1-Weighted Image FLAIR were comparable but statistically superior to those obtained with T1-Weighted Spin Echo imaging whether on the CNR lesion- white matter with p value 0,043 or lesion-gray matter with p value 0,015.